2009
DOI: 10.1088/0004-637x/692/1/894
|View full text |Cite
|
Sign up to set email alerts
|

A Cr-K EMISSION LINE SURVEY IN YOUNG SUPERNOVA REMNANTS WITHCHANDRA

Abstract: We performed a Cr-K emission line survey in young supernova remnants (SNRs) with the Chandra archival data. Our sample includes W49B, Cas A, Tycho and Kepler. We confirmed the existence of the Cr line in W49B and discovered this emission line in the other three SNRs. The line center energies, equivalent widths (EWs) and fluxes of the Cr lines are given. The Cr in Cas A is in a high ionization state while that in Tycho and Kepler is in a much lower one. We find a good positive correlation between Cr and Fe line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…Since no photon emissivity data existed for the He-like stages of Co or Mn, Hwang et al (2000) estimated emissivities by interpolating the emissivity data generated for Ca, Fe, Ni by the Raymond and Smith thermal models Raymond & Smith 1977; these were then used to infer the abundances of these elements. Subsequently, Cr line emission has been reported for W49B, Tycho's SNR, Kepler's SNR, and Cas A with Chandra observations (Yang et al 2009). Generally the Cr ion states (as estimated by the centroid energy of the Cr emission in these moderate-resolution CCD spectra) track the ion stages of Fe in the same objects and range from an estimated Ne-like to He-like ions.…”
Section: Introductionmentioning
confidence: 94%
“…Since no photon emissivity data existed for the He-like stages of Co or Mn, Hwang et al (2000) estimated emissivities by interpolating the emissivity data generated for Ca, Fe, Ni by the Raymond and Smith thermal models Raymond & Smith 1977; these were then used to infer the abundances of these elements. Subsequently, Cr line emission has been reported for W49B, Tycho's SNR, Kepler's SNR, and Cas A with Chandra observations (Yang et al 2009). Generally the Cr ion states (as estimated by the centroid energy of the Cr emission in these moderate-resolution CCD spectra) track the ion stages of Fe in the same objects and range from an estimated Ne-like to He-like ions.…”
Section: Introductionmentioning
confidence: 94%
“…However, recently Tamagawa et al (2009) reported the detection of chromium (Cr, Z = 24) and manganese (Mn, Z = 25) Kα line emission from Tycho's SNR using Suzaku data ( Fig. 23, see also Yang et al, 2009). The nucleosynthesis of Mn is influenced by the presence of the neutron rich element 22 Ne, whose abundance is determined by the metallicity of the white dwarf progenitor.…”
Section: Type Ia Supernova Remnants 81 X-ray Spectroscopy Of Type Iamentioning
confidence: 99%
“…After submitting our paper for publication, we became aware of an independent paper by Yang et al (2009) on the same subject on the Cr-K line. Their conclusions are very similar to those presented here: Cr and Fe are colocated.…”
Section: Cr-k Linementioning
confidence: 99%